2020
DOI: 10.1136/bmjopen-2019-032513
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary approach to mental illness: do inflammation, telomere length and microbiota form a loop? A protocol for a cross-sectional study on the complex relationship between inflammation, telomere length, gut microbiota and psychiatric disorders

Abstract: IntroductionSevere psychiatric disorders are typically associated with a significant reduction in life expectancy compared with the general population. Among the different hypotheses formulated to explain this observation, accelerated ageing has been increasingly recognised as the main culprit. At the same time, telomere shortening is becoming widely accepted as a proxy molecular marker of ageing. The present study aims to fill a gap in the literature by better defining the complex interaction/s between inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The recruitment process of our cohorts of 38 patients affected by SCZ and 20 HC took place at the community mental health center of the Section of Psychiatry of the Department of Medical Science and Public Health, University of Cagliari and University Hospital Agency of Cagliari and was previously detailed [ 35 ]. The study was conducted according to the guidelines of the Declaration of Helsinki, in compliance with the Italian national legislation, and approved by the Ethics Committee of the University Hospital Agency of Cagliari (PG/2018/11693, 5th of September 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The recruitment process of our cohorts of 38 patients affected by SCZ and 20 HC took place at the community mental health center of the Section of Psychiatry of the Department of Medical Science and Public Health, University of Cagliari and University Hospital Agency of Cagliari and was previously detailed [ 35 ]. The study was conducted according to the guidelines of the Declaration of Helsinki, in compliance with the Italian national legislation, and approved by the Ethics Committee of the University Hospital Agency of Cagliari (PG/2018/11693, 5th of September 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, twenty healthy control (HC) subjects were recruited through word of mouth among hospital staff, their families, and university students. Assessment procedures have been detailed in Manchia et al [21]. Briefly, patients were included in the study if: (1) they had a diagnosis of MDD according to Diagnostic and statistical manual of mental disorders DSM-IV-TR (DSM IV-TR) [22] criteria; (2) were able to express a consent to participate formulated by signing the consent form; (3) were of age between 18 and 70 years old; (4) were in euthymic phases.…”
Section: Participantsmentioning
confidence: 99%
“…Accelerated TL shortening has been noted in chronic inflammation and patients with depression. Depressive patients also display detrimental changes in gut microbiota, which subsequently modify the gut–brain communication and inflammatory responses. In this context, Manchia et al recently suggested the importance of the TL, inflammation, and gut microbiota triad in the development of mental disorders . Thus, considering a strong interlink between telomere biology and neuropsychiatric illnesses, a literature review on this subject is valuable for an early diagnosis, timely interventions, and developing new therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Manchia et al recently suggested the importance of the TL, inflammation, and gut microbiota triad in the development of mental disorders. 13 Thus, considering a strong interlink between telomere biology and neuropsychiatric illnesses, a literature review on this subject is valuable for an early diagnosis, timely interventions, and developing new therapeutics. Herein, we comprehensively discuss three key features: (i) involvement of inflammation in depression; (ii) role of gut dysbiosis and increased intestinal permeability in depression; and (iii) telomere attrition in depression (Figure 1).…”
Section: Introductionmentioning
confidence: 99%